Optimizing light delivery through fiber bundle in photoacoustic imaging with clinical ultrasound system: Monte Carlo simulation and experimental validation - Sivasubramanian, Kathyayini (2017)
Translating photoacoustic (PA) imaging into clinical setup is a challenge. We report an integrated PA and ultrasound imaging system by combining the light delivery to the tissue with the ultrasound probe. First, Monte Carlo simulations were run to study the variation in absorbance within tissue for different angles of illumination, fiber-to-probe distance (FPD), and fiber-to-tissue distance (FTD). This is followed by simulation for different depths of the embedded sphere (object of interest). Several probe holders were designed for different light launching angles. Phantoms were developed to mimic a sentinel lymph node imaging scenario. It was observed that, for shallower imaging depths, the variation in signal-to-noise ratio (SNR) values could be as high as 100% depending on the angle of illumination at a fixed FPD and FTD. Results confirm that different light illumination angles are required for different imaging depths to get the highest SNR PA images. The results also validate that one can use Monte Carlo simulation as a tool to optimize the probe holder design depending on the imaging needs. This eliminates a trial-and-error approach generally used for designing a probe holder.